2010
DOI: 10.1590/s0365-05962010000300002
|View full text |Cite
|
Sign up to set email alerts
|

Úlcera de Buruli

Abstract: Buruli ulcer, an infectious disease caused by Mycobacterium ulcerans, is the third most prevalent mycobacteriosis, after tuberculosis and leprosy. This atypical mycobacteriosis has been reported in over 30 countries, mainly those with tropical and subtropical climates, but its epidemiology remains unclear. The first autochthonous cases of infection in Brazil have recently been described, making this diagnosis important for Brazilian dermatologists. Clinical manifestations vary from nodules, areas of edema, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…BU pathogenesis is mediated by mycolactone, a potent polyketide-derived macrolide that triggers apoptotic cell death [ 2 ] and is associated with the necrotic nature of the disease [ 3 ]. BU mostly affects people in tropical countries in Africa [ 4 ], America [ 5 ], Asia [ 6 ] and Australia [ 7 ]. Although no official estimate of global incidence is available at present, West Africa is the main endemic area, with 1967 new cases reported by Côte d'Ivoire, Ghana, and Benin in 2013[ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…BU pathogenesis is mediated by mycolactone, a potent polyketide-derived macrolide that triggers apoptotic cell death [ 2 ] and is associated with the necrotic nature of the disease [ 3 ]. BU mostly affects people in tropical countries in Africa [ 4 ], America [ 5 ], Asia [ 6 ] and Australia [ 7 ]. Although no official estimate of global incidence is available at present, West Africa is the main endemic area, with 1967 new cases reported by Côte d'Ivoire, Ghana, and Benin in 2013[ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“… The recovery of infected individuals is assumed to occur both spontaneously and through treatment. Research has shown that localized lesions may spontaneously heal but, without treatment, most cases of Buruli ulcer result in physical deformities that often lead to physiological abnormalities and stigmas [ 4 ]. …”
Section: Methodsmentioning
confidence: 99%
“…Buruli ulcer (BU), a necrotic skin disease caused by Mycobacterium ulcerans , is the third most prevalent mycobacterial infection after tuberculosis and leprosy [1]. It has been reported in West Africa, Central Africa, East Africa, Australia, China, South America and Japan with West Africa being the most endemic region [2].…”
Section: Introductionmentioning
confidence: 99%